Type I complex regional pain syndrome. - Gaspar, Ana Teresa (2012)
Type I complex regional pain syndrome is a neurophatic pain syndrome whose physiopathology is not yet fully understood. It mainly affects limb extremities and often occurs after local trauma. There is no consensus on the treatment, but early intervention seems important, particularly in the context of Physical Medicine and Rehabilitation. The authors review physiopathologic mechanisms and point to importance of an early diagnosis, since failure to recognize this clinical picture and the consequent delay in treatment may cause serious functional impairments.